The role of genetic factors in pediatric myelodysplastic syndromes with different outcomes - Ying Li; Li Cheng; Yun Peng; Lin Wang; Wenzhi Zhang; Yuhong Yin; Jing Zhang; Xiaoyan Wu (BMC Pediatrics, 2024)
Abstract Background Pediatric myelodysplastic syndromes (MDS) are rare disorders with an unrevealed pathogenesis. Our aim is to explore the role of genetic factors in the pathogenesis of MDS in children with different outcomes and to discover the correlation between genetic features and clinical outcomes as well as disease characteristics. Methods We conducted an analysis of archived genetic data from 26 patients diagnosed with pediatric MDS at our institution between 2015 and 2021, examining the association between different genetic characteristics and clinical manifestations as well as prognosis. Additionally, We presented three cases with distinct genetic background and outcomes as examples to elaborate the role of genetic factors in pediatric MDS with different prognoses. Results Genetic variations were detected in 13 out of the 26 patients, including 8 patients with co-occurrence of somatic and germline mutations (CSGMs) and 5 patients with somatic mutations alone. Our analysis revealed that advanced MDS (4/8, 50% vs. 1/5, 20% and 4/11, 36.4%), PD (3/8, 37.5% vs. 1/5, 20% and 1/11 9.1%), and TD (6/8, 75% vs. 2/5, 40% and 2/11, 18.2%) were more common in patients with CSGMs than those with somatic mutations alone or without any mutations. We also found out in our study that 8 patients with CSGMs had evidently different clinical outcomes, and we presented 3 of them as examples for elaboration. Case 1 with germline and somatic mutations of unknown significance had a relatively slow disease course and a good prognosis. Case 2 with compound heterozygous germline SBDS variants and somatic mutations like del20q had a stable disease course and a reversed outcome. Case 3 with a germline GATA2 variant and somatic mutations including − 7 had a rapidly progressive disease course and a worst prognosis. Conclusion Our findings indicate that genetic background of pediatric MDS is closely linked with disease characteristics as well as outcomes and that CSGMs may lead to disease progression. It should be emphasized that the interaction between certain germline variants and somatic mutations, such as SBDS and del20q, may result in hematopoietic stem cell adaptation (improved hematopoiesis) and reversed clinical outcomes, which can facilitate the development of targeted therapy.